Relationships among migration properties, molecular structure and catalytic process of isotactic copolymers of propene. (September 2016) - Talarico, Giovanni; de Ballesteros, Odda Ruiz; De Rosa, Claudio; Auriemma, Finizia; Malafronte, Anna; Pirozzi, Beniamino; Serroni, Gaspare; Trifuoggi, Marco
Graphical abstract: Commercial grades of isotactic propene-ethylene copolymers for food packaging show outstanding mechanical properties but migration of highly defective and short chains by contact with fatty foods. This is due to the multi-site heterogeneous Ziegler-Natta catalytic process. The migration is reduced by treatment of pellets with heptane at 50 °C. The treatment exploits fractional crystallization, entropy driven depletion of the lamellar stacks formed by long chains, and consequent rejection of short chains at the boundaries. Highlights: The structure, thermal and mechanical properties of ethylene/propene copolymers. Correlation with the migration properties. The migrating species are highly defective copolymer chains with low molecular mass and high ethylene content. A simple chemical route to allow the iPP-based materials to fall within the overall migration limit is proposed. Abstract: Isotactic polypropylene-based (iPP) materials find large applications for the food packaging. In this article the structure, thermal and mechanical properties of some commercial grades of ethylene/propene copolymers produced by heterogeneous Ziegler-Natta (ZN) catalysis, have been characterized. These grades can be potentially used for manufacturing food containers. However, despite the desired performances in terms of mechanical and optical properties, we found that the samples exceed the overall migration limit set by the EU Directive into isooctane, used as fatty food simulant. The migrating species are highly defective copolymer chains with low molecular mass and high ethylene content. The migration is intrinsically related to the presence of fractions generated by the heterogeneous multisite surface of the ZN catalysts. A simple chemical route to allow the iPP-based materials to fall within the overall migration limit is proposed.